The serendipity of moribund political vulnerable: the plight of displaced children during the liberation struggle for Zimbabwe. (1970-1980) - Mazambani, Ishmael (Midlands State University, 2016)
To children who were exploited, neglected, abandoned ,mistreated, abused, mutilated, sexually abused, forced to take part in the killing of others, displaced and forced to abandon their homes in fear of death and torture, life in their homes and in refugee camps was unbearable. This study wishes to demonstrate that displaced children during the liberation struggle faced violence, abuse, exploitation, marginalization, injustice, oppression and repression which forced them to abandon their homes to seek salvation in neighboring countries where their plight worsened rather than improved. Children who were refugees had in most cases lost everything, families, relatives, homes, friends and a sense of belonging. A harrowing and haunting past was their only baggage they had when they fled into refugee camps where life was also associated with humanitarian crisis. The plight of displaced children during the liberation struggle for Zimbabwe has largely escaped the attention of historians yet these children who were exposed to multiple dangers have a war time story to tell. Their stories have totally been forgotten when the history of the liberation struggle for Zimbabwe is being discussed. The study largely depended on oral interviews of those who were below the age of eighteen and were displaced by the liberation struggle across Rhodesia, archival sources and secondary sources.